(untitled) (Repertorio Científico, 2024)
The first edition of the Taxathon (rapid ecological inventory) in the La Sabana Metropolitan Park of San José, Costa Rica, aimed to record the largest number of species of flora and fauna in this urban park during two days of sampling. In the case of mammals, two sampling methods were carried out: Trail walks to obtain direct observations and specific sampling methodologies such as trap cameras, Sherman traps, Tomahawk trap and fog nets. In total, 11 individuals corresponding to five species were registered; two corresponded to fruit bats (Artibeus jamaicensi and Sturnira parvidens) and one to a nectar-eating bat (Glossophaga commissarisi). It was also possible to register a hairless fox (Didelphis marsupialis) and four individuals of variable squirrels (Sciurus variegatoides). All of these species are relatively common and were part of the expected results for a study in an urban environment. It is recommended to increase the sampling effort for next editions of the Taxathon (sites, time, people) in order to have a greater possibility of registering more quantity and variety of mammals.